PERAN PASAR DESA DALAM PENINGKATAN EKONOMI PEDAGANG MENURUT PERSPEKTIF EKONOMI ISLAM (Studi Kasus Pedagang Pasar Selasa, Desa Karang Puri, Kecamatan Wonoayu, Kabupaten Sidoarjo) - Indah Ajeng Pratiwi Ate; Ani Faujiah (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
This Tuesday Market is the first market, the Lumping Horse art community and is enough to attract the attention of the wider community. Seeing the public's interest in the performance of horse lumping art and bazaar, the youths of Karang Puri village took the initiative to turn the bazaar into a night market and a performance of Kuda Lumping art. After the market was running, many residents proposed to open the market in the morning so that mothers would not have trouble finding daily necessities. In addition, the existence of this market helps the karangpuri community to get or open a business as a trader, cart builder, etc. Looking at the background of the problem, the question arises, what is the role of the market in improving the economy of traders and what is the view of the islamic economy on the economic behavior of market traders tuesday in an effort to improve the economy of traders. The type of research that the author uses is field research (field research) which is the role of the Tuesday market is very beneficial for society especially in the economic sector. The survey found that merchants take on four roles namely: the products sold are varied, as jobs, and buyer dependence, strategic time and place. From the perspective of Islamic Economics, the Tuesday market of karang puri village applies ketauhidan and conducts healthy competition. The policy of Prohibiting Unfair Competition in The Commercial System and Islamic Sharia is regulated in Law No. 5/1999. Because it can harm society and destroy the State. Keywords: Role, Village Market, Islamic Economy, Trader, Improvement References Hulwati, (2009), Ekonomi Islam: Teori dan Praktiknya dalam perdagangan Obligasi Syari’ah di Pasar Modal Indonesia dan Malaysia, Padang: Ciputat Press Group. Kartini Kartono, (1996), Pengantar Metodologi Riset Sosial, Bandung: CV Mundur Maju. Lexy J. Moleong, (2009), Metodologi Penelitian Kualitatif, Bandung: PT. Remaja Rosdakarya, Edisi Revisi. Maskuroh Nikmatul, skripsi : “peran pasar tradisoanal dalam peningkatan perekonomian masyarakat menurut perspektif ekonomi islam”, IAIN Metro Universitas Sumatra Utara, “Kemiskinan”, http://repossitory.usu.ac.id Syed Nawab Haider Naqvi, (2009), Menggagas Ilmu Ekonomi Islam, terj. M. Saiful Anam dan Muhammad Ufuqul Mubin, Yogyakarta: Pustaka Pelajar. Thamrin Abdullah dan Francis tantri, (2014), Manajemen Pemasaran Depok: PT Raja Grafindo Persada. Muhammad, (2007), Prinsip-prinsip Ekonomi Islam, Yogyakarta: Graha Ilmu. Mustafa Edwin Nasution dkk, (2006), Pengenalan Eksklusif Ekonomi Islam, Jakarta: kencana.